(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2024)
Objective: To evaluate the effects of high intensity interval training (HIIT) on body composition in employees of the company Almidones de Sucre during the pandemic of 2021. Methodology: A quantitative correlational and cross-sectional study; a 12-week HIIT programme was implemented with 30 participants, evaluating changes in body composition by measuring % body fat, bone weight, muscle weight and residual weight with ISAK I restricted profile. A pretest and posttest of the intervention was applied, and descriptive and inferential analyses, including ANOVA and Pearson’s correlation tests, were applied. Results: The results showed a significant reduction in body fat percentage from 24.2% to 21.4% (p < 0.05) and an increase in muscle percentage from 40.8% to 43.0% (p < 0.05). No significant changes in bone weight or residual weight were observed. High correlations between Pretest and Posttest (r > 0.85) indicated consistency in the data. Discussion: The findings are consistent with previous studies highlighting the efficacy of HIIT in improving body composition and metabolic health. The reduction in % body fat and increase in muscle weight suggest that HIIT is an effective strategy for improving physical fitness in a relatively short period of time, even in the context of pandemic restrictions. Conclusion: HIIT training is presented as an effective intervention for improving physical fitness in a relatively short period of time, even in the context of pandemic restrictions.